Aplicação de modelo matemático na difusão de inovação tecnológica através das equações diferenciais ordinárias - ALBUQUERQUE, Ederson Gonçalo Lima (2023)
The diffusion of technological innovation studied through models that in its composition uses ordinary differential equations as the mathematical logistic model that will be used to model the behavior of bibliographic data from netflix and whatsapp and with this will be the case study about these two companies. Thus, the development of this research may lead more people to develop new works with mathematical models to analyze or make predictions about the contemporary phenomenon studied. The case study will be a quantitative approach where the research of company data will be collected through the Internet and with this have a phenomenological analysis of the diffusion of technological innovation from the common differential equations where the bibliographic | data will be analyzed and interpreted from the graphs constructed through the Qtiplot software to obtain the results of the parameters of the sigmoid function when it is adjusted to the data of the companies.